The effects of l-name on nicotine-induced locomotor sensitization in mice - Ulusu, Umut; Uzbay, İ. Tayfun; Karakaş, Sirel (Journal of Dependence, 2003)
Objective: The aim of the present study is to investigate the effects of NG-nitro-arginine -mehyl-ester (L-NAME), a nitric oxide synthase (NOS) inhibitor, on nicotine-induced locomotor sensitization in mice. Thus, a possible effect of nitric oxide (NO) in nicotine-induced locomotor sensitization and/or nicotine dependence has been studied.Method: Adult female Swiss-Webster mice were used as subjects. All study was performed in three sections. In the first section of the study, the effective dose of nicotine for locomotor sensitization was determined. In the second section, the effects of L-NAME on nicotine-induced locomotor sensitization in mice were evaluated. The effects of L-NAME on locomotor activity were also investigated in naive (no nicotine injected) mice in the third section. Nicotine (0.5, 1 and 2 mg/kg), L-NAME ( 15, 30 and 60 mg/kg) or saline were injected to mice intraperitoneally. Immediately following the substance or saline injections, mice were put into the locomotor activity cages and locomotor activity was measured for 30 minutes. In the first and second section of the study substances or saline were administrated to mice (10 times at two days intervals). In the third section of the study, acute injections were administrated.Results: Nicotine (1 mg/kg) was found as the most effective dose on the locomotor sensitization. Pretretment of L-NAME (15-60 mg/kg) blocked the nicotine (1 mg/kg)-indu- ced locomotor sensitization. L-NAME (15-60 mg/kg) did not produce any significant change on the locomotor activity of the naive mice.Conclusion: In this study, L-NAME, a NOS inhibitor agent, blocked nicotine-induced locomotor sensitization in mice without producing any nonspesific effect as sedation. Our study also imply that NO may have an important contribution in nicotine dependence and NOS inhibitory agents such as L-NAME may be potential drugs for the treatment of nicotine dependence.
Keywords: Nicotine; locomotor sensitization; nitric oxide; L-NAME; mice